A high-throughput newborn screening approach for SCID, SMA, and SCD combining multiplex qPCR and tandem mass spectrometry - Tesorero, Rafael; Janda, Joachim; Hörster, Friederike; Feyh, Patrik; Mütze, Ulrike; Hauke, Jana; Schwarz, Kathrin; Kunz, Joachim; Hoffmann, Georg F.; Okun, Jürgen G. (PLOS ONE, 2023)
Early diagnosis of severe combined immunodeficiency (SCID), spinal muscular atrophy (SMA), and sickle cell disease (SCD) improves health outcomes by providing a specific treatment before the onset of symptoms. A high-throughput nucleic acid-based method in newborn screening (NBS) has been shown to be fast and cost-effective in the early detection of these diseases. Screening for SCD has been included in Germany’s NBS Program since Fall 2021 and typically requires high-throughput NBS laboratories to adopt analytical platforms that are demanding in terms of instrumentation and personnel. Thus, we developed a combined approach applying a multiplexed quantitative real-time PCR (qPCR) assay for simultaneous SCID, SMA, and 1st-tier SCD screening, followed by a tandem mass spectrometry (MS/MS) assay for 2nd-tier SCD screening. DNA is extracted from a 3.2-mm dried blood spot from which we simultaneously quantify T-cell receptor excision circles for SCID screening, identify the homozygous SMN1 exon 7 deletion for SMA screening, and determine the integrity of the DNA extraction through the quantification of a housekeeping gene. In our two-tier SCD screening strategy, our multiplex qPCR identifies samples carrying the HBB: c.20A>T allele that is coding for sickle cell hemoglobin (HbS). Subsequently, the 2nd tier MS/MS assay is used to distinguish heterozygous HbS/A carriers from samples of patients with homozygous or compound heterozygous SCD. Between July 2021 and March 2022, 96,015 samples were screened by applying the newly implemented assay. The screening revealed two positive SCID cases, while 14 newborns with SMA were detected. Concurrently, the qPCR assay registered HbS in 431 samples which were submitted to 2nd-tier SCD screening, resulting in 17 HbS/S, five HbS/C, and two HbS/β thalassemia patients. The results of our quadruplex qPCR assay demonstrate a cost-effective and fast approach for a combined screening of three diseases that benefit from nucleic-acid based methods in high-throughput NBS laboratories.
Gesehen am 07.07.2023